2013
DOI: 10.1002/piq.21152
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Model Comparison of Expert and Novice Performance Improvement Practitioners

Abstract: This study investigates the mental model comparison between expert and novice performance improvement practitioners. Nonexperimental survey research design was applied. Based on specific criteria, 11 critical concepts out of 30 were selected by 23 experts. Sixteen of those 23 experts provided data about the relatedness of 55 concept‐pairs generated from the 11 concepts to develop the common mental model of experts in the Knowledge Network Organizing Tool utilizing Pathfinder scaling. Two‐hundred‐forty‐two prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Fishermen who are considered experts in either advanced or traditional fishing techniques are well-grounded in the do's and don'ts of their respective fishing practices. Expert mental models therefore reflect a more coherent structure than novice mental models as a result of their collective knowledge and information (Toker, 2012). Experts thus attempt to construct abstract knowledge representations while non-experts attempt to construct more concrete ones (Palmer & Pickett, 1999).…”
Section: Using Mental Models To Understand Malaysian Fishermen's Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishermen who are considered experts in either advanced or traditional fishing techniques are well-grounded in the do's and don'ts of their respective fishing practices. Expert mental models therefore reflect a more coherent structure than novice mental models as a result of their collective knowledge and information (Toker, 2012). Experts thus attempt to construct abstract knowledge representations while non-experts attempt to construct more concrete ones (Palmer & Pickett, 1999).…”
Section: Using Mental Models To Understand Malaysian Fishermen's Fishmentioning
confidence: 99%
“…Abstraction is constructed as experts possess more conceptual knowledge and more information within those conceptions. Expert mental models therefore reflect a more coherent structure than novice mental models as a result of their collective knowledge and information (Toker, 2012). Nevertheless, fishermen who use traditional methods and those who use more modern technologies can both develop and be guided by expert mental models; however, the content of the models will be different based on differences in experience.…”
Section: Using Mental Models To Understand Malaysian Fishermen's Fishmentioning
confidence: 99%
“…The cognitive maps of HPI experts were explored by Villachica et al in 2001; the finding was that a key central concept was "Focus on results. " Toker and Moseley ( 2013 ) researched the similarities and differences between the mental models of novice and expert HPI professionals. The results indicated that the mental models of novices were primarily linear and rules based.…”
Section: Expert and Expertisementioning
confidence: 99%
“…The cognitive mapping of Villachica et al ( 2001 ) and the mental model research of Improvement, 2015a,b ). Toker and Moseley ( 2013 ) relate to ISPI's first Standard to "Focus on results or outcomes" (International Society for Performance Improvement, 2015a,b ). Finally, notice that Toker and Moseley's ( 2013 ) findings on the characteristics of the mental models of HPI experts-holistic, structurally consistent, central branching-relate to all of the ISPI Standards and to the second one in particular; "take a systemic view" (International Society for Performance Improvement, 2015a,b ).…”
Section: Expert and Expertisementioning
confidence: 99%
See 1 more Smart Citation